Reactivity Descriptors for the Activity of Molecular mn4 Catalysts for the Oxygen Reduction Reaction - Zagal-Moya, J; Zagal-Moya, J (Wiley-VCH Verlag, 2016)
Similarities are established between well-known reactivity descriptors of metal electrodes for their activity in the oxygen reduction reaction (ORR) and the reactivity of molecular catalysts, in particular macrocyclic MN4 metal complexes confined to electrode surfaces. We show that there is a correlation between the MIII/MIIredox potential of MN4 chelates and the M-O2binding energies. Specifically, the binding energy of O2(and other O species) follows the MIII-OH/MIIredox transition for MnN4 and FeN4 chelates. The ORR volcano plot for MN4 catalysts is similar to that for metal catalysts: catalysts on the weak binding side (mostly CoN4 chelates) yield mainly H2O2as the product, with an ORR onset potential independent of the pH value on the NHE scale (and therefore pH-dependent on the RHE scale); catalysts on the stronger binding side yield H2O as the product with the expected pH-dependence on the NHE scale. The suggested descriptors also apply to heat-treated pyrolyzed MN4 catalysts. © 2016 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim